Ethnopolitical discourse among ordinary Malaysians: diverging accounts of "the good-old days" in discussing multiculturalism - Hashim, Azirah (De Gruyter, 2013)
A small group of ethnically diverse Malaysians was assembled to discuss the state of multiculturalism in Malaysia. Discursive analysis was used to get at the participants' accounting practices and constructions of multiculturalism. Participants' accounts revealed an increasing social distance between the Malays and the non-Malays, but differing assessments and explanations for such group boundaries. Participants' accounts drew on both their own experiences and on broader ethnopolitical discourses to tell their side. Participants used various voicing practices to represent or evaluate the current situation and how it became this way. Religion, especially Islam, was used as an ethnopolitical discourse and was articulated in different ways. For instance, the Malays invoked being Muslim as the primary source of identity and imagined community, while the non-Malays cited the politicization of Islam as a cause for the increasing boundary between groups. Despite these differences participants seemed willing to engage on these "sensitive issues" through criticism and defensive accounts sequences.